MODELING OF ACUTE ASPIRATION BRONCHOPNEUMONIA - Pensky, Paul; Lytvynets, Mykhailo; Musienko, Daria; Zyablitsev, Sergey (The Ukrainian Scientific Medical Youth Journal, 2021)
There is currently an urgent need to create an available experimental model to reproduce the main pathogenetic mechanisms of COVID-associated lung injury. The first stage of such a model may be the reproduction of acute aspiration bronchopneumonia in rats. Aim – to establish an effective and biologically safe model of acute aspiration bronchopneumonia. Methods. A group of laboratory Wistar rats (n=20) with full observance of bioethical norms under thiopental anesthesia underwent surgery with the introduction into the trachea of sterile nylon thread 2.5 cm long and 0.2 mm thick to a depth of 2.5 cm; in the control group included 5 animals. On days 7 and 21, the animals were removed from the experiment, made pathomorphological, cytological and hematological studies. The MedStat program (USA) was used for statistical surveys. Results. During the observation, the animals developed cyanosis of the skin and mucous surfaces, breathing became difficult with the active involvement of the respiratory muscles, severe rales and crepitation were heard. Rectal temperature increased by 1-1.5oC. On the 21st day, the granulocyte-lymphocyte index increased (1.5 times; p=0.003). On sectional examination after 7 days, the lungs were swollen, pale pink in color, had layers of fibrin, severe cyanosis, intra-tissue hemorrhage. After 21 days, these changes were supplemented by the development of atelectasis and fibrosis. Cytological examination showed proliferation of fibrous tissue with activation of biosynthetic processes, severe dystrophy of the bronchial epithelium, lymphoid infiltration. Conclusion. The model of acute aspiration bronchopneumonia in rats allows to obtain the main clinical and morphological manifestations of acute lung damage with cyanosis, shortness of breath, wet wheezing and crepitation, and in the lungs – edema, hemorrhage, active fibrosis.